PENGARUH LINGKUNGAN SOSIAL TERHADAP PENDIDIKAN MASYARAKAT DI DESA BIONTONG I KECAMATAN BOLANGITANG TIMUR KABUPATEN BOLAANG MONGONDOW UTARA - PAKAYA, INDAH; POSUMAH, JOHNNY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2021)
Abstract: The purpose of this study was to determine the influence of the Social Environment on CommunityEducation in Biontong I Village, East Bolangitang District, North Bolaang Mongondow Regency. Thisresearch uses quantitative methods. The study consisted of two variables, namely the social environment(family environment, school environment, community environment) as the independent variable andcommunity education as the dependent variable. Respondents of the study were 40 residents of Biontong IVillage, East Bolangitang District, who were taken using a proportional random sampling technique.Instruments and data collection techniques using a questionnaire and assisted by interview quides, andobservation. The analysis technique for testing the hypothesis used statistical analysis of multiple regressionand multiple correlation. The results of the study concluded: (1) The social environment (family environment,school environment, community environment) has a positive and significant effect on community education.This means that the better the conditions of the social environment, the better the conditions of publiceducation; (2) The social environment (family environment, school environment, community environment) iscorrelated and has a strong and significant power of determination on the development of communityeducation. That is, the condition of public education at the dominant level is determined by the conditions ofthe social environment.Keywords: Social Environment, Community Education